Kinematic Characteristics of Sperm in Bali Bulls (Bos sondaicus) Aged Over 10 Years Based on Computer-Assisted Sperm Analysis - Sulistiyawati, Elis; Prastiya, Ragil Angga; Sardjito, Trilas; Saputro, Amung Logam; Maxdhameta, Styuderil Imaniro; Habib, Mohammad Nabil El; Sasi, Samira Musa; Sulistyowati, Deny; Amaliya, Anny (Faculty of Animal Science, Universitas Brawijaya, 2026)
Bali cattle, developed in Indonesia, are renowned for their high parasite resistance, adaptability, and reproductive health. This study aimed to evaluate the impact of age on the kinematic parameters of sperm in Bali bulls post-thawing. Semen samples were obtained by artificial vagina methods from three Bali bulls aged between 11 and 13 years, whose age was not indicated, and one bull of 9 years, which was used as a control. The experiment was conducted in December 2023 at the Singosari National Artificial Insemination Center in Malang, East Java, for sperm parameters, including viability, motility, and morphology. Computer-assisted sperm analysis was performed. The results showed a decline in sperm quality from fresh to frozen semen. Despite this, the semen from Bali bulls met the Indonesian National Standard, demonstrating the bulls' superior reproductive capabilities. Bulls aged 11–13 years exhibited variations in sperm quality; however, these differences may reflect individual variability rather than a consistent age-related trend. Semen from bulls aged over 10 years remain suitable for use, though regular testing is essential. Further research is needed to understand these variations and ensure optimal semen quality across different ages.